ADVANCE CARE PLANNING, A STEP-BY-STEP GUIDE FOR HEALTH CARE PROFESSIONALS ASSISTING PATIENTS WITH CHRONIC CONDITIONS TO PLAN FOR CARE TOWARDS END OF LIFE. Issue 2 (1st June 2013) - Greeve, K; Bloomer, S; Chellew-Hawley, M; Clarnette, R; Fortnum, D; Garton-Smith, J; Harney, M; Ibrahim, J; Kendall, P; Koay, A; Moody, H; Porter, S; et al.
Abstract : Background: Advance Care Planning encourages people to think about, and discuss their preferred about future health care. Many patients rely on their health professionals to initiate ACP discussions, however most health professionals lack the skills required for such discussions. Aim: To improve uptake of ACP amongst healthcare professionals in WA Health. Methods: An ACP Chronic Disease Reference Group was established to provide leadership of the project. Interviews were conducted with reference group members to identify the barriers to ACP and identify patient groups who would benefit. A literature search was undertaken to identify prognostic indicators and issues relevant to target patient groups. These outputs were assessed against a multidisciplinary panel of stakeholders and the ACP reference group. Results: Chronic heart failure, chronic lung disease, renal disease and neurodegenerative conditions were identified as priorities for additional ACP resources. Specific and general prognostic indicators were identified which could act as triggers for initiating ACP conversations. Medical and lifestyle considerations relevant to specific conditions were identified and discussion prompts provided. Finally, guidance regarding documentation and dissemination of the outputs of these discussions was considered. Discussion: A guide on its own as a resource will not drive a culture change within health. A model of ACP, consistent with national and international literature, and acknowledging the barriers to ACP is required. Conclusion: To address issues in communication and education, an ACP model which assists in the identification of patients who may benefit from ACP and issues relevant to those with chronic diseases has been developed.